2020
DOI: 10.25258/ijpqa.11.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Role-Playing in Pharmacy

Abstract: Role-play refers to a situation that allows learners to examine realistic situations by interacting with other individuals in a controlled way to develop experience and try different strategies within a supported environment. Depending on the objective of the activity, learners may play a role that is related to their own or could take on an opposite part as well. In this study, the author sought to investigate the satisfaction and perception of pharmacy students toward role-playing. The study used a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…35 Furthermore, simulation-based exercises, such as the role-play and standardized patient scenario used in some trainings, can improve student pharmacists' communication skills 36 and ability to effectively convey their knowledge. 37 Five of the seven trainings reported since the last review were rated of "good" quality; however, they could be improved by incorporating validated assessment measures and clearly defined objective outcomes that can be observed and rated by blinded coders. Additionally, most of the studies in this review used self-reported data that were gathered shortly post-training, which could be impacted by social desirability bias.…”
Section: Discussionmentioning
confidence: 99%
“…35 Furthermore, simulation-based exercises, such as the role-play and standardized patient scenario used in some trainings, can improve student pharmacists' communication skills 36 and ability to effectively convey their knowledge. 37 Five of the seven trainings reported since the last review were rated of "good" quality; however, they could be improved by incorporating validated assessment measures and clearly defined objective outcomes that can be observed and rated by blinded coders. Additionally, most of the studies in this review used self-reported data that were gathered shortly post-training, which could be impacted by social desirability bias.…”
Section: Discussionmentioning
confidence: 99%
“…In their view, this would lessen the burden of their impromptu conversations, whilst guaranteeing conversation quality and preventing them from going off-topic. According to Alshammari ( 24 ), highly detailed role-plays in a pharmacy context would also make students more dependent. An unintended consequence might be that students perceive the task to be less difficult.…”
Section: Discussionmentioning
confidence: 99%
“…The use of real-life scenarios and the inclusion of multidisciplinary teams during training have shown improvements in the skills of healthcare professionals [ 69 ]. In the same way, studies including role-play as part of the training have demonstrated improved professional skills (e.g., recognition of possible scenarios and solutions, increased confidence and communication skills, promoted effective discussion, and active participation) [ 70 , 71 ]. Despite this, some studies assessing pharmacists’ confidence to provide mental health services using self-assessment tools have identified that participants often overestimate their confidence to deliver the services in practice after training [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%